Strategies for Successful Catheterization Laboratory Recovery From the COVID-19 Pandemic - Poulin, Marie-France (JACC Cardiovasc Interv, 2020)
As the world slowly starts to recover from the coronavirus disease-2019 pandemic, health care systems are now thinking about resuming elective cardiovascular procedures, including procedures in cardiac catheterization laboratories. Rebooting catheterization laboratories will be an arduous process, in part because of limited health care resources, new processes, and fears stemming from the coronavirus disease-2019 pandemic. The authors propose a detailed phased-in approach that considers clinical, patient-centered, and operational strategies to safely and effectively reboot catheterization laboratory programs during these unprecedented times. This model balances the delivery of essential cardiovascular care with reduced exposure and preservation of resources. The guiding principles detailed in this review can be used by catheterization laboratory programs when restarting elective interventional procedures.